2011
DOI: 10.1002/term.399
|View full text |Cite
|
Sign up to set email alerts
|

Effects of transforming growth factor-β subtypes on in vitro cartilage production and mineralization of human bone marrow stromal-derived mesenchymal stem cells

Abstract: Human bone marrow stromal-derived mesenchymal stem cells (hBMSCs) will differentiate into chondrocytes in response to defined chondrogenic medium containing transforming growth factor-β (TGFβ). Results in the literature suggest that the three mammalian subtypes of TGFβ (TGFβ1, TGFβ2 and TGFβ3) provoke certain subtype-specific activities. Therefore, the aim of our study was to investigate whether the TGFβ subtypes affect chondrogenic differentiation of in vitro cultured hBMSCs differently. HBMSC pellets were cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 34 publications
1
48
0
1
Order By: Relevance
“…Mueller and Tuan performed an in-depth study investigating the contribution of TGF-b and dexamethasone, both constituents of the in vitro culture medium employed in the current study, concluding that the resultant MSC-derived chondrogenic pellets recapitulate EO in vitro [21]. More recently, Cals et al have demonstrated that individual TGF-b subtypes orchestrate in vitro terminal differentiation [52]. Exploitation of these observations has lead to the in vitro chondrogenic priming of MSCs, followed by subsequent implantation and natural ossification, as an improved method to engineer bone for regenerative applications [24,53].…”
Section: Discussionmentioning
confidence: 60%
“…Mueller and Tuan performed an in-depth study investigating the contribution of TGF-b and dexamethasone, both constituents of the in vitro culture medium employed in the current study, concluding that the resultant MSC-derived chondrogenic pellets recapitulate EO in vitro [21]. More recently, Cals et al have demonstrated that individual TGF-b subtypes orchestrate in vitro terminal differentiation [52]. Exploitation of these observations has lead to the in vitro chondrogenic priming of MSCs, followed by subsequent implantation and natural ossification, as an improved method to engineer bone for regenerative applications [24,53].…”
Section: Discussionmentioning
confidence: 60%
“…While it is perhaps unsurprising that the delivery of BMP2 appeared to support a more osteogenic phenotype 29,52 , the finding that pTGF-β3 delivery supported a similar phenotype was less expected. It is likely that the combination of the osteogenic stimulus provided by the nHA, with the overexpression of pTGF-β3 led to promotion of hypertrophic/osteogenic differentiation in the MSCs 53 . In contrast, nHA-mediated co-delivery of pTGF-β3 and pBMP2 resulted in suppressed calcification and collagen type X deposition, and promoted a more stable chondrogenic phenotype characterized by increased GAG and collagen type II production.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] Chondrocyte-related growth factors such as transforming growth factor β, 17 bone morphogenetic proteins, 18 and insulin-like growth factor 19 play a critical role in developing an appropriate microenvironment in cartilage tissue engineering. 20 However, the uncontrolled delivery of these factors may decrease their full reparative potential and have unwanted morphological effects. 21,22 To regulate the release of factors, loading microparticle containing factors into the scaffolds 23 and covalently binding the factors to the scaffolds have been used in recent research of chondrogenesis.…”
Section: Introductionmentioning
confidence: 99%